Monetary Policy with an Endogenous Capital Stock When Inflation Is Persistent. - Mash, R (Department of Economics (University of Oxford), 2002)
The paper presents a monetary policy model with an endogenous capital stock when a backward looking element in wage setting causes inflation persistence. We analyse how the endogeneity of the capital stock changes the macroeconomic dynamics with which policy interacts and its implications for optimal policy and time inconsistency. Capital stock endogeneity makes inflation more persistent in reduced form. This makes the optimal contemporaneous policy response to shocks more vigorous but the subsequent return to steady state more gradual. Observed output becomes more serially correlated. Capital endogeneity can also give rise to disinflation bias under discretion for some parameter values.